2 × 2 Tables: a note on Campbell's recommendation. (17th November 2015) - Busing, F. M. T. A.; Weaver, B.; Dubois, S.
Abstract : For 2 × 2 tables, Egon Pearson's N − 1 chi‐squared statistic is theoretically more sound than Karl Pearson's chi‐squared statistic, and provides more accurate p values. Moreover, Egon Pearson's N − 1 chi‐squared statistic is equal to the Mantel‐Haenszel chi‐squared statistic for a single 2 × 2 table, and as such, is often available in statistical software packages like SPSS, SAS, Stata, orR, which facilitates compliance with Ian Campbell's recommendations. Copyright © 2015 John Wiley & Sons, Ltd.